Pemanfaatan Terapi Komplementer (Pijat Oksitosin Menggunakan Minyak Essensial Lavender) Sebagai Upaya Untuk Meningkatkan Produksi Asi Pada Ibu Nifas - Ariu Dewi Yanti; Meylina Rohmatul H; Vivi Misya A (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem that postpartum mothers often face regarding lactation is not achieving exclusive breastfeeding, one of which is due to irregular milk production. The decrease in breast milk production and release is caused by a lack of stimulation of the hormones prolactin and oxytocin which play a role in the smooth production and release of breast milk. Results of community service carried out on September 20 2024 in Carangrejo Village, Kesamben District, Jombang Regency using the Pre-post one group design method. From the results of the pre-test carried out, 14 of the 20 respondents (70%) postpartum mothers did not understand and did not know about complementary therapy for mothers. And the post test results, after being given education and demonstrations about complementary therapy, showed that 19 respondents (95%) understood the benefits of complementary therapy (Oxytocin massage using lavender essential oil). Based on the results of the community service program that has been implemented, it was found that there was an increase in knowledge among postpartum mothers about the benefits of complementary oxytocin massage therapy using lavender essential oil for postpartum mothers.